Unraveling the dynamics: Exploring the nexus between abusive supervision, counterproductive work behaviors and the moderating influence of mindfulness - Junça Silva, A.; Encarnação, C. (Journal of Managerial Psychology, 2024)
Purpose Relying on the affective events theory, this study conceptualizes abusive supervision as a micro-affective event and tests a multilevel moderated mediation arguing that abusive behaviors from the supervisor trigger negative affective reactions that, in turn, will enhance the likelihood of counterproductive work behaviors (interpersonal and organizational). We further propose that mindfulness will shape how employees react to abusive behaviors from supervisors. Design/methodology/approach A daily diary study conducted for five consecutive days was developed with Portuguese working adults (N = 176*5 = 880). Findings The multilevel findings showed that abusive behaviors triggered negative affect and this, in turn, promoted both forms of counterproductive work behaviors. The indirect effect regarding interpersonal counterproductive work behavior was moderated by mindfulness in such a way that the indirect effect was stronger for those who scored lower on mindfulness (versus higher levels). The indirect effect on organizational counterproductive work behavior was not significantly moderated by mindfulness. Practical implications The examination of mindfulness as a moderating factor contributes significantly to management by delineating practical strategies to assist employees in effectively managing micro-events involving abusive behaviors from supervisors. Consequently, these findings may inform the development of research-backed strategies aimed at mitigating the affective and behavioral repercussions of an abusive supervisor. Originality/value The inclusion of mindfulness in the model is an added value.